PENGARUH VARIASI LATIHAN TERHADAP HASIL SERVICEATASPEMAIN BOLA VOLI KLUB MAKMUR JAYA KECAMATAN TIUMANG USIA 15-17 TAHUN - Desi Tri Susanti; Fauziah Fauziah; Yelvia Prahagia (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2022)
ABSTRACT The purpose of this study was to determine the effect of training variations on the results of top service on volleyball players at Club Makmur JayaTiumang District aged 15-17 years. The study was conducted 3 times a week with a frequency of 18 meetings. The method used in this study is an experimental method that uses a hypothesis test, namely the T-test. The research was carried out at the Makmur Jaya Volleyball club, Tiumang District with a sample of 12 people. The results of the study were based on hypothesis testing which was carried out on the initial test and the post-test of top service in data analysis using the t-test where the initial test obtained an average of 18.1 points and the final test obtained an average of 22.8 points. While the Tcount is 5.33 when compared to Ttable of 1.79, it is clear that there is an increase because the initial test and the final test have different results. Based on the results of the research and discussion that has been carried out, it can be concluded that the variation of training program has an influence on the results of top service on volleyball players at Club Makmur JayaTiumang District aged 15-17 years. Keywos :Exercise Variations, Top Service Results.